2019
DOI: 10.1186/s12879-018-3660-1
|View full text |Cite
|
Sign up to set email alerts
|

Burden and risk factors of invasive group B Streptococcus disease among neonates in a Chinese maternity hospital

Abstract: BackgroundThere is a lack of data regarding the prevalence of invasive group B streptococcus (GBS) infection among neonates in China. This study aimed to investigate the incidence and mortality of invasive GBS infection and to identify the risk factors in our hospital.MethodsSeventy-four cases admitted between January 2011 and December 2016 was included in this study. A retrospective matched case-control study was conducted in a tertiary maternity and paediatric hospital. Risk factors for the acquisition of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…GBS is a leading cause of neonatal sepsis, pneumonia, and meningitis (9)(10)(11)(12)(13)(14). Recent data also suggest that GBS is a frequent cause of chorioamnionitis, endometritis, pneumonia, and urosepsis in adults with underlying medical conditions (i.e., diabetes mellitus or immunosuppression) (15)(16)(17)(18)(19). As these patterns of pathogenesis suggest, GBS is considered a saprophytic organism, i.e., invasive GBS disease is most commonly observed in weakened hosts.…”
mentioning
confidence: 99%
“…GBS is a leading cause of neonatal sepsis, pneumonia, and meningitis (9)(10)(11)(12)(13)(14). Recent data also suggest that GBS is a frequent cause of chorioamnionitis, endometritis, pneumonia, and urosepsis in adults with underlying medical conditions (i.e., diabetes mellitus or immunosuppression) (15)(16)(17)(18)(19). As these patterns of pathogenesis suggest, GBS is considered a saprophytic organism, i.e., invasive GBS disease is most commonly observed in weakened hosts.…”
mentioning
confidence: 99%
“…In the current study, S. agalactiae was the second most frequently isolated pathogen causing neonatal sepsis, contributing to 21% of the isolates. Other studies also reported S. agalactiae as the most common aetiology of neonatal sepsis [ 29 , 30 , 31 ]. In contrast, S. agalactiae has rarely been reported in other studies conducted in Tanzania [ 10 , 16 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 95%
“…However, it was noted that most cases in neonatal sepsis in maternal and child health care hospital were EOS, and GBS accounted 16.7% in pathogen distribution, significantly higher than in national and regional general hospital. GBS emerges to be the leading pathogen of maternal disease and neonatal sepsis in Chinese population since universal maternal GBS screening (38)(39)(40). It is known that maternal GBS colonization is the risk factor of neonatal sepsis, therefore, intrapartum antibiotic treatment has been an important strategy for management of neonatal EOS (8, 41).…”
Section: Discussionmentioning
confidence: 99%